Synergistic reinforcement of in situ ZrB2 particles and Sc on the corrosion behaviour of 7N01 alloy - Anjun Shi; Xizhou Kai; Ran Tao; Yicheng Fan; Yutao Zhao (Journal of Materials Research and Technology, 2023)
In this study, the effects of in situ ZrB2 particles and rare earth element Sc on the corrosion behavior of 7N01 alloy were investigated separately, with the characteristics of their synergistic enhancement being elucidated. The introduction of Sc into the ZrB2/7N01 composites led to an enhancement in both the distribution and morphology of the in situ particles, with the size of ZrB2 particles being significantly reduced and large particle clusters almost disappearing compared to the situation without Sc addition. A decrease in the grain size of the matrix alloy 7N01 from 170 μm to 33 μm was also observed when the Sc addition was 0.5 wt%. The low corrosion susceptibility observed after the addition of Sc was attributed to the refinement of grains and the inhibition of the formation of precipitate-free zones. The addition of ZrB2 improved corrosion resistance by promoting the precipitation of Al3Sc precipitates. Importantly, it was found that the 7N01 alloy with 3 wt% ZrB2 and 0.5 wt% Sc exhibited high mechanical properties and admirable corrosion resistance, which makes it a promising material for various applications. In summary, this study highlighted the individual and combined effects of in situ ZrB2 particles and rare earth element Sc on the corrosion behavior of 7N01 alloy, with valuable insights being provided for the development of advanced structural composite materials.